Rabi Maize and its Yielding Ability - Anuradha, K.; Naik, M. Ramesh; Teja, R. Ravi (Chronicle of Bioresource Management, 2020)
Maize, the “queen of cereals,” has found a new throne in India’s winter fields. rabi maize, which was traditionally a kharif crop, has becoming more common because of its excellent growing conditions, which increase yields and economic benefits. These favorable conditions, includes mild temperatures and reduced pest pressure. This allows for better water management, enhanced nutrient uptake, and improved plant stand establishment. With yields often surpassing those of kharif maize, rabi maize offers not only economic benefits but also plays a crucial role in agricultural diversification and sustainability. Despite challenges like climate change and market volatility, rabi maize holds immense potential for boosting agricultural productivity and farmer incomes. This winter crop is not just a testament to agricultural innovation but a crucial step towards ensuring food security and sustainable farming practices in India.